Community movement to prevent stunting in the area of Tambaksari District Puskesmas Rangkah Surabaya - Queen Khoirun Nisa' Mairo; Yuni Ginarsih; Sherly Jeniawaty; Astuti Setiyani; Dwi Purwanti; Ervi Husni; Ani Media Harumi; Ira Rahayu Tiyar Sari; Ira Puspitasari; Ratna Sari; Juliana Christyaningsih (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Stunting refers to the condition of a child's height being shorter than the height of his age, which is caused by a lack of nutritional intake for a long time in the first 1000 days of life (HPK), diabetes, or kidney failure; hampering Indonesia's demographic bonus where the ratio of the non-working age population to the working age population decreases; threat of reducing intelligence level by 5-11 points. In addition to nutritional factors, stunting is caused by a lack of public knowledge, especially pregnant women, mothers of toddlers and posyandu cadres. The purpose of this community empowerment is to increase the knowledge of posyandu cadres and the community in the Rangkah Surabaya Health Center area through health promotion by forming the Community Movement Prevent Stunting (GEMAS), academic and technical related to the implementation of Posyandu. The provision of stunting education is expected to be able to carry out posyandu activities optimally on target. Cadre education activities showed an increase in general knowledge of posyandu cadres, attitudes and actions of cadres and knowledge about stunting.